Academic challenges of visually impaired students at Hail University - Alsamiri, Yasir A.; Alduaylij, Abdulrahman bin Ali bin Abdullah (Jurnal Cakrawala Pendidikan, 2025)
This study investigated the academic experiences of visually impaired students at Hail University, addressing a critical gap in understanding accessibility challenges in Saudi higher education. The research aimed to identify barriers in three key areas: learning material accessibility, exam accommodation effectiveness, and faculty awareness of student needs. Using a qualitative phenomenological approach, semi-structured interviews were conducted with five visually impaired students selected through purposive sampling. Data were collected through in-depth interviews and validated using member checking and peer debriefing techniques. Thematic analysis revealed several significant barriers: (1) inconsistent accessibility of digital course materials, with 80% of students reporting difficulties with PDF documents and presentation slides; (2) limitations in exam accommodations, particularly insufficient time allowances and inadequate screen reader compatibility; and (3) varying levels of faculty awareness, with only 20% of instructors proactively addressing accessibility needs. The study's novelty lies in its comprehensive examination of the intersection between digital accessibility, academic accommodations, and faculty preparedness in a Middle Eastern university context, providing insights previously unexplored in Saudi Arabian higher education. The findings contribute to developing evidence-based recommendations for improving institutional support systems and faculty training programs, ultimately enhancing educational experiences for visually impaired students in similar institutional contexts.